Promises from a playboy - Laurence, Andrea (Laurence, Andrea. Switched!., 2021)
Losing his memory after a plane crash might be the best thing that ever happened to Finn Steele. Because when Willow Bates offers him shelter, she opens his heart in ways never before possible. His fascination with the reclusive mystery writer is tempered by Willow's wariness and vulnerability. Surrendering to desire becomes the ultimate act of trust. But when Finn's former life as a billionaire womanizer comes to light, will it be the ultimate betrayal?